p38 MAPK Signaling in Osteoblast Differentiation - Rodríguez-Carballo, Eddie; Gámez, Beatriz; Ventura, Francesc (Frontiers in Cell and Developmental Biology, 2016)
The skeleton is a highly dynamic tissue whose structure relies on the balance between bone deposition and resorption. This equilibrium, which depends on osteoblast and osteoclast functions, is controlled by multiple factors that can be modulated post-translationally. Some of the modulators are Mitogen-activated kinases (MAPKs), whose role has been studied in vivo and in vitro. p38-MAPK modifies the transactivation ability of some key transcription factors in chondrocytes, osteoblasts and osteoclasts, which affects their differentiation and function. Several commercially available inhibitors have helped to determine p38 action on these processes. Although it is frequently mentioned in the literature, this chemical approach is not always as accurate as it should be. Conditional knockouts are a useful genetic tool that could unravel the role of p38 in shaping the skeleton. In this review, we will summarize the state of the art on p38 activity during osteoblast differentiation and function, and emphasize the triggers of this MAPK.